DYNAMIC CHARACTERISTICS SIMULATION ANALYSIS AND MICROSCOPIC MODEL OF RUBBER CONVEYOR BELT OF STEEL CORE - CHEN HongYue; ZHANG Kun; LI EnDong; LI YongHong; MAO Jun (Jixie qiangdu)
It is the key for the development of green energy-saving belt conveyor to analysis and research on the rubber conveyor belt of steel core about its dynamic characteristics. Mathematical model of the rubber conveyor belt of steel core were established based on the space coordinate transformation theory. Then 3-D microscopic virtual simulation model were established by using parametric modeling, scanning and tensile of Pro/E software. The Moonery-Rivlin and Bilinear Isotropic model of ANSYS were used to define attribute about rubber covering and wire rope. Simulated dynamic characteristics of rubber conveyor belt of steel core under sinusoidal pressure by setting tied between wire rope and rubber covering. The result show that, under the axial displace load, the axial deformation of steel core presented layered distribution trend along wire rope section. The axial deformation of side strand’s side wire presented two-time-helix change distribution. Every side strand deformation amount was almost same and axial deformation of side strand’s side wire gradually enlarged along handed, the axial deformation amount of side strand changed remarkably relative to Core strand. The axial deformation amount of rubber covering exist little deformation amount in the middle port and large deformation amount all around. The average axial deformation of rubber is larger than the deformation amount of wire rope. which reveal mechanism of energy consumption about rubber conveyor belt of steel core, then that provide theoretical basis for research and development of green energy-saving belt conveyor.